2013
DOI: 10.1002/pc.22800
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of carbon black and carbon-silica dual phase filler in natural rubber matrix

Abstract: In this article, the synergistic effects of carbon black (CB) and modified carbon-silica dual phase filler (MCSDPF) on the properties of natural rubber (NR) were investigated. MCSDPF was prepared by modifying carbon-silica dual phase filler (CSDPF) with bis(3-triethoxysilylpropyl)tetrasulphane (Si-69). Fourier transform infrared spectroscopy and thermogravimetric analyzer analyses revealed that Si-69 was successfully grafted to CSDPF. NR-based compounds containing various combinations of MCSDPF and CB were pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 30 publications
(36 reference statements)
1
12
0
Order By: Relevance
“…Figure shows the bound rubber content of A x SiO 2 /NR compounds. It is found that bound rubber content of A 2 SiO 2 /NR compound reaches maximum with a 48% increment, compared to that of unmodified nSiO 2 /NR compound, which suggests the strongest interaction between NR and A 2 SiO 2 . The coverage of AMI on the surface of nSiO 2 may largely restrain the interaction between the filler nanoparticles and strengthen the filler–rubber interaction.…”
Section: Resultsmentioning
confidence: 91%
“…Figure shows the bound rubber content of A x SiO 2 /NR compounds. It is found that bound rubber content of A 2 SiO 2 /NR compound reaches maximum with a 48% increment, compared to that of unmodified nSiO 2 /NR compound, which suggests the strongest interaction between NR and A 2 SiO 2 . The coverage of AMI on the surface of nSiO 2 may largely restrain the interaction between the filler nanoparticles and strengthen the filler–rubber interaction.…”
Section: Resultsmentioning
confidence: 91%
“…The increment of silica loading in the weight ratio of silica/palm ash enhances the rubber–filler interaction, tensile properties, shorter curing time, and fatigue life of NR hybrid composites. It has been shown that the NR, styrene butadiene rubber (SBR), and NBR vulcanizates containing silica/CB give better overall mechanical properties and good balance in the properties compared to those having only 50 phr of silica or CB. The explanation is given as the better filler dispersion as a result of the lower development of filler network in the vulcanizates.…”
Section: Introductionmentioning
confidence: 99%
“…(a)), the peak at 3406 cm −1 corresponds to the O–H stretching frequency of Si–OH and C–OH groups on the surface of CSDPF . After the modification by Si69, the broad peak at 3406 cm −1 disappears in the spectrum of Si69‐CSDPF, which indicates the success of covalent interaction between −OH groups of CSDPF and Si69 . The Si69 will further react with NR chain during cure processing, causing the covalent bond between filler and NR finally.…”
Section: Resultsmentioning
confidence: 99%
“…For Si69‐modified CSDPF (Si69‐CSDPF), 50‐g CSDPF was dispersed into ethanol by sonication at 40°C for 1 h; then 0.8‐g Si69 was gradually added, mechanical stirred under 55°C for another 6 h . After reaction, the mixture was filtrated and then washed with ethanol to scour off the redundant Si69.…”
Section: Methodsmentioning
confidence: 99%